A Study Case Of First Language Acquisition: A Two-Year-Old Child - Luhur, Ayu Nirmala; Ediwan, I Nyoman Tri; Laksminy, Luh Putu (Denpasar Institute, 2024)
The acquisition of language involves multiple cognitive and linguistic processes. In this process, children learn the sound system of their language, how words are used to represent meaning, and how words can be combined to form sentences. This study discussed first language acquisition in a child aged two years old based on phonological, morphological, and semantics aspects. This study aims to determine how children develop as they acquire the first language and to analyze the vocabulary and simple sentences mastered by two-year-old children based on linguistic features, i.e., phonology, morphology, and semantics. The descriptive qualitative method and theory of cognitive development by Chomsky were used to analyze the data in this study. The data source was obtained by using observation and note-taking techniques to observe and note the utterances of a girl named Anastasia Gabriella Putri Wahyudi. Based on the research results, Anna’s language acquisition is significantly influenced by the family environment. In addition, Anna’s linguistic development is progressing well, with phonological, morphological, and semantic features that are typical for a two-year-old child